ITPR1 variant-induced autosomal dominant hereditary spastic paraplegia in a Chinese family - Li, Rui; Liu, Xuan; Ke, Chenming; Zeng, Fanli; Zeng, Qingyi; Xu, Xiaowei; Fan, Xiaoqin; Zhang, Ying; Hou, Qinghua (Frontiers in Neurology, 2024)
Hereditary spastic paraplegia (HSP) is a rare neurodegenerative disease prominently characterized by slowly progressive lower limbs weakness and spasticity, the significant genotypic and phenotypic heterogeneity of this disease makes accurate diagnosis of it very challenging. We identified a NM_001168272: c.2714A>G (chr3.hg19: g.4716912A>G) mutation variant in inositol 1,4,5-triphosphate receptor type 1 (ITPR1) gene in a three-generation Chinese HSP family with many individuals affected, which has never been reported to be associated with the pathogenesis of HSP. And we applied whole exome sequencing (WES), copy number variants (CNV) assay, dynamic mutation analysis to the whole family, and protein structure prediction to make it confirmed. This finding expanded the clinical and genetic spectrum of HSP. Variant identified in the present study is in the coupling-domain, and the present study comprises the first on-the spot corroborated report assigning ITPR1 variants to HSP.